Pengaruh Influencer Marketing, Online Customer Review, Dan Persepsi Harga Terhadap Keputusan Pembelian The Originote Hyalucera Moisturizer (Studi Kasus Mahasiswa FEB UNISMA Angkatan 2020) - Yuliansyah, Febriana Putri; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The study aims to find out the impact of Influencer Marketing, Online Customer Review, and Price Perceptions on Purchase Decisions The Originote Hyalucera Moisturizer Case Study Students of the Faculty of Economics and Business of Islamic University of Armed Forces 2020. The method used in this study is a quantitative method using a Slovin formula of 87 respondents. The study used SPSS data analysis methods in analyzing normality tests, classical assumption tests, hypothesis tests, double linear regression tests and adjusted R2 coefficient tests. The results showed that Influencer Marketing influences purchasing decisions, Online Customer Review influences purchase decisions, and Price Perception does not influence purchasing decision. Keywords: Influencer Marketing, Online Customer Review, Price Perception, Purchase Decision